PERBANDINGAN MODEL PEMBELAJARAN DISCOVERY LEARNING DAN PROBING PROMPTING TERHADAP KEAKTIFAN BELAJAR SISWA - Widya Destiyanti Adjie; Nurmala R (Mathematics Education And Application Journal (META), 2020)
AbstractThis research is a quasi-experimental research (quasi experimental), which aims to look at the comparison of discovery learning models and probing prompting to the learning activities of class IX MTs DDI Tarakan students. The results of descriptive analysis before being treated with an average achievement of student learning activeness in experimental class 1 using discovery learning models is 30.34% and in experimental class 2 using probing prompting learning models is 27.17%. For the average percentage of the two experimental classes are both in the less active category. Descriptive analysis results after being treated with an average achievement of student learning activeness in experimental class 1 using discovery learning models higher that is equal to 53.5% included in the active category of the experimental class 2 using the probing prompting learning model is 43,14 % is in the inactive category. For the average achievement of all indicators of student learning activeness for experimental class 1 is higher than in ekaperimne 2. So the discovery learning model is better than the probing prompting learning model for the learning activeness of class IX MTs DDI Tarakanstudents. Keywords: Experiments, Discovery Learning Learning Model, Probing Prompting Learning Model, Student Learning Activity AbstrakPenelitian ini merupakan penelitian eksperimensemu (quasi esperimental),yang bertujuan untuk melihat perbandingan model pembelajaran discovery learning dan probing prompting terhadap keaktifan belajar siswa kelas IX MTs DDI Tarakan. Hasil analisis deskriptifsebelum diberi perlakuan dengan rata-rata pencapaian keaktifan belajar siswa dikelas eksperimen 1 yang menggunakan model pembelajaran discovery learningadalah 30,34% dan pada kelas eksperimen 2 yang menggunakan model pembelajaran probing prompting adalah27,17%. Untuk rata-rata persentase kedua kelas eksperimen tersebut sama-sama berada pada kategori kurang aktif. Hasil analisis deskriptif setelah diberi perlakuan dengan rata-rata pencapaian keaktifan belajar siswa dikelas eksperimen 1 yang menggunakan model pembelajaran discovery learninglebih tinggi yaitu sebesar53,5%termasuk dalam kategori aktif dari pada kelas eksperimen 2 yang menggunakan model pembelajaran probing prompting adalah43,14% termasuk dalam kategori kurang aktif.Untuk rata-rata pencapaian dari seluruh indikator keaktifan belajar siswa untuk kelas eksperimen 1 lebih tinggi dibandingkan pada kelas ekaperimne 2. Jadi, model pembelajaran discovery learning lebih baik dibandingkan model pembelajaran probing prompting terhadap keaktifan belajar siswa kelas IX MTs DDI Tarakan.